Localization of Buddhism in China—The Case of Pingcheng in The Northern Wei Dynasty (Journal of Global Arts Studies, 2024)
Background: The eastward transmission of Buddhism through the cultural influence of Gandhara promoted the translation of Buddhist scriptures and the missionary activities of monks traveling between East and West. In addition, the Northern Wei regime’s policy of population migration contributed to the communal and multicultural nature of Pingcheng society, thereby stimulating the prosperity of Buddhist beliefs and Buddhist activities during the Northern Wei Dynasty. During the Pingcheng period, Buddhism penetrated state governance, royal culture, and popular society, while both the quality and quantity of Buddhist statues reached a remarkably high level. Objective: This paper aims to analyze the evolution of Buddhist art styles from the historical background of ethnic integration during the Northern Wei Dynasty through an artistic perspective, reflecting the interactive relationship between ethnic integration and artistic transformation. The study focuses on Buddhist statues from the Pingcheng period of the Northern Wei Dynasty and examines the process of their localization. Methods: Through an analysis of stylistic changes in representative statues from the early, middle, and late stages of the Yungang Grottoes, the study further investigates the developmental process and social factors related to the worship of significant Xianbei figures in the Five Caves of Tan Yao, while exploring the localization process of Buddhist art in Pingcheng. Results: The population relocation policies implemented under cultural transplantation led to the convergence and integration of multiple cultures in Pingcheng, thereby promoting the flourishing peak of Buddhist art during the Northern Wei Dynasty. Conclusion: The diachronic changes observed in the statues of the Yungang Grottoes demonstrate that the localization of Buddhism was not merely a simple accumulation or passive inheritance of foreign Buddhist doctrines, but rather a creative transformation rooted in the cultural soil of the Chinese nation. The localization and development of Buddhist statues in Pingcheng during the Northern Wei Dynasty exerted a profound and lasting influence on the study of multicultural integration in Chinese history.
Keywords: Chinese Buddhism; Localization; Pingcheng of Northern Wei Dynasty; Cultural integration